STRATEGI PENINGKATAN MANAJEMEN MUTU DI SEKOLAH DASAR MUHAMMADIYAH KARANGKAJEN IV - Utaminingrum, Ratna (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
This study aims to: 1.) Assess the quality improvement of educational institutions at SD Muhammadiyah Karangkajen IV 2.) Find alternative formulations of strategic management of Muhammadiyah educational institutions in improving school quality. This research is a case study research that is qualitative in nature, using the methods of observation, interviews and documentation of Muhammadiyah educational institutions. The data analysis technique uses the theory of Miles and Huberman with the stages of data reduction, data presentation and conclusions. The results of the study indicate that the management of quality management in schools is input, process and output that involves all stakeholders. The school first formulates the school's vision and mission by considering the internal and external factors of the school environment, then formulating the goals and targets of school quality followed by determining the strategy that will be used by the school for the realization of all agreed quality targets. The implementation of the strategy carried out by SD Muhammadiyah Karangkajen IV in improving the quality of schools is to describe and implement all the strategies that have been formulated in the form of programmed and measurable activities. The evaluation of the strategy used by SD Muhammadiyah IV is through formal and informal meetings.